Creative fashion drawing : a complete guide to design and illustration styles - Chapman, Noel (Arcturus Pub., Ltd., 2014)
An introduction to fashion design illustration, with step-by-step instruction on poses, fabrics, accessories, clothing design, and using templates for flats.